The use of interactive methods for development of future specialists’ creativity (The Journal of Psychology and Sociology, 2019)
The article discusses the best ways to use interactive methods in higher education for the development of creativity of future specialists. The basic conditions for the implementation of the goal of effective use of interactive methods,taking into account the basic requirements of active learning.From a psychological point of view of external indicators of the effectiveness of interactive learning tend to interact with future professionals, recognizing the collective behavior of a group developing reflexes, developing collective cooperation and understanding rights and responsibilities the future professionals as internal indicators of interactivity, the willingness to work, which leads to the development of selfreflection that becomes the subject of educational activities.To solve it, first of all, it is necessary to update the content of the educational process, and the best method is to develop the personality, skills, creativity and talent of each person. Only then will higher education institutions be able to educate citizens who are able to make changes in their lives and choose their own way of life.Key words: creativity, interactive methods, personality, attitudes, abilities.